EVALUATING THE RESULTS OF PERIPHERALLY INSERTED CENTRAL CATHETER TECHNIQUE AND RELATED FACTORS IN NEONATES AT PHU THO PROVINCIAL OBSTETRICS AND PEDIATRICS HOSPITAL (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the results of peripherally inserted central catheter technique and describe factors related to the results of insertion and maintenance of peripherally inserted central catheter in neonates at Phu Tho provincial Obstetrics and Pediatrics Hospital in 2025.Methods: A cross-sectional descriptive study analyzed over 120 cases of peripherally inserted central catheter in 116 neonates from January 2024 to September 2025.Results: The majority of peripherally inserted central catheter placements were successful (96.7% after intervention). 80.8% of catheters were in the correct central position immediately after insertion. The average duration of catheter maintenance was 18.1-19.35 days. The rate of central line-associated bloodstream infection was significantly higher in neonates with lower gestational age (p = 0.026) and lower birth weight (p = 0.021). Non-central tip position increased the risk of infection by 3.9 times compared to central position (p = 0.017).Conclusion: Peripherally inserted central catheter is a highly effective technique for long-term infusion in neonates. Low birth weight, low gestational age, and non-central catheter tip position are significant risk factors for complications, especially central line-associated bloodstream infection.
Keywords: PICC, neonates, CLABSI, Phu Tho provincial Obstetrics and Pediatrics Hospital.